Race pace control by means of a new chronometer system - Perez, P.; Llana, S.; Zahonero, J. (Biomechanics and Medicine in Swimming X, 2006)
This paper describes a new chronometer System that provides feedback in real time and without interfering with the swimmer's execution. The System consists on a leds screen (water resistant) installed on the bottom of the pool, so that swimmers can see it every time they perform a turn. This System can be connected to a PC or PDA, which permits register lap times for further analysis. Feedback provided by the chronometer to control swimming speed was compared with the condition "traditional feedback" provided by the coach and with the condition "no feedback". Results show little dispersion on lap time with this new kind of feedback at aerobic swimming speed. At an anaerobic threshold swimming speed, dispersion was similar between "traditional feedback" and Chronometer feedback, and a little more dispersion in "no feedback" condition.